Related party transactions and finance company failure: New Zealand evidence. Issue 2 (3rd April 2018) - Bhuiyan, Md. Borhan Uddin; Roudaki, Jamal
Abstract : Purpose: This paper aims to examine the existence of related party transactions (RPTs) in failed financial companies in New Zealand when firms have interlocking directors on the board. We also examine the role of auditors in the review of RPTs. We anticipate that inter-company director relationships promote RPTs, while reputable large auditors (i.e. Big4) restrict the practice. Design/methodology/approach: This study uses multivariate analysis to examine the determinants of RPTs. We use an unique, hand-collected database of New Zealand finance companies all of which collapsed during the years 2006-2011. Findings: Using a sample of 65 firms (including 38 failed finance firms) and 219 firm-year observations, we found that almost half of the failed finance firms were engaged in RPTs. For the failed firms, those that were engaged in RPTs were mostly represented by interlocking directors and were audited by non-Big4 auditors, implying lower monitoring quality may facilitate RPTs. Using a sub-sample, we also found evidence that firms engaged in RPTs were later convicted of questionable accounting and disclosure practices. Practical implications: This research is beneficial to regulators and audit professionals in understanding the potential for adverse outcomes associated with interlocking directors and undisclosed RPTs. While interlocking directors could enrich the external connections of a firm which might facilitate capital resourcing, this study suggests regulators might encourage firms to disclose RPTs when the firm has higher interlocked directors. Originality/value: This study is the first to examine the association between RPTs and interlocking directors using a sample of failed finance companies. RPTs and lack of disclosure were widely attributed with being the determinants of corporate failure in the finance sector. However, failed finance firms remain widely under-researched because of a lack of available data. This study circumvent this limitation by using print media and business news portals to collate information on RPTs and interlocking directors. While prior research indicates that weak corporate governance leads to poor accounting practice, using the interlocking board as a proxy for weak corporate governance, this study is the first to substantiate the adverse effect of interlocking boards and undisclosed RPTs with corporate failure.